Unusual resistance to ionizing radiation of the viruses of kuru, Creutzfeldt-Jakob disease, and scrapie. - Gibbs, C J (1978)
The titers of several preparations of kuru. Creutzfeldt-Jacob disease, and scrapie viruses were reduced by only 1/10th or less by high doses of gamma radiation of 50 kGy and by only 1/10th-1/1000th or less for 200 kGy. This unusual radiation resistance of the two human viruses further links them with the scrapie virus and suggests that the genetic information of all three viruses is considerably smaller than that of any other known viruses of mammals.